A wheat dominant dwarfing line with Rht12, which reduces stem cell length and affects gibberellic acid synthesis, is a 5AL terminal deletion line. (15th January 2019) - Sun, Linhe; Yang, Wenlong; Li, Yafei; Shan, Qiangqiang; Ye, Xiaobin; Wang, Dongzhi; Yu, Kang; Lu, Weiwen; Xin, Peiyong; Pei, Zhong; Guo, Xiaoli; Liu, Dongcheng; et al.
Summary: Dwarfing and semi‐dwarfing are important agronomic traits that have great potential for the improvement of wheat yields. Rht12, a dominant gibberellic acid (GA)‐responsive dwarfing gene from the gamma‐ray‐induced wheat mutant Karcagi 522M7K, is located in the long arm of chromosome 5A, which is closely linked with the locus Xwmc410 . Rht12 is likely an ideal gene for GA biosynthesis and deactivation research in common wheat. However, information on the Rht12 locus and sequence is lacking. In this study, Rht12 significantly shortened stem cell length and decreased GA biosynthetic components. Using bulked segregant RNA‐Seq, wheat 660k single nucleotide polymorphism chip detection, and newly developed simple sequence repeat markers, Rht12 was mapped to a 11.21‐Mb region at the terminal end of chromosome 5AL, and was found to be closely linked with the Xw5ac207 SSR marker with a 10.73‐Mb fragment deletion in all of the homologous dwarfing plants. Transcriptome analyses of the remaining 483‐kb region showed significantly higher expression of the TraesCS5A01G543100 gene encoding the GA metabolic enzyme GA 2‐β‐dioxygenase in dwarfing plants than in high stalk plants, suggesting that Rht12 reduces plant height by activating TaGA2ox‐A14 . Taken together, our findings will promote cloning and functional studies of Rht12 in common wheat. Significance statement: The wheat dominant dwarfing gene, Rht12, reduces stem cell length and decreases bioactive gibberellic acid synthesis, mapped in a region with a 10.73‐Mb fragment deletion on chromosome 5AL terminal.